Conference for Computer Aided Engineering and System Modeling.: 9th Figes Users' Conference, Swissotel, The Bosphorus, Istanbul, December 09-10,2004 : Conference Proceedings / vol. I-II - 9th Figes Users' Conference. Istanbul, Turkey. December 09-10-2004
9th Figes Users' Conference CD.-vol. I - II
CD-Rom disk
eng